“Beer is Haram!” Representation of Islam by Online Newspapers in Malaysia on the issue of better Beer festival & oktoberfest - Muhammad Raqib Mohd Sofian,; Nurul Nadirah Abu Hasan,; Afiqah Mior Kamarulbaid,; Muhamad Zaki Mustafa,; Nurul Fathihin Mohd Noor Shah,; Norsimaa Mustaffa, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The representation of Islam in the media has been widely discussed by media scholars. In the Malaysian context, Islam is frequently associated with conflicts resulting from political issues or actions taken by religious authorities against any organisation or individual that sparks public debate. The government is also alleged to use Islam as a hegemonic tool to continue dominating the mindset of the lower class by using religion as a political weapon to gain power and maintain the status quo. Newspapers especially those owned by the government have certain ideologies to convey to the general public in order to maintain a specific existing social order. This causes the controversial issues pertaining to Islam to be frequently discussed in the news media in tandem with the vested interest of those owning the newspapers. However, the discourse on issues involving Islam has become more daring after the emergence of digital news portals that enable hegemonic counterarguments to be discussed widely among members in the mentioned medium. Therefore, the purpose of this study is to explore how Islam and Muslims are represented in online newspapers in Malaysia. Two samples from English-language online newspapers, namely The Star Online and Malaysiakini, were selected. By using quantitative and qualitative content analysis, the findings of this study show that Islam, Islamic political parties, and some Muslims in Malaysia have been represented as extremists and backwards by online newspapers.